Insights into Optimal Schemes of Radial Network Arch Pedestrian Bridge - Rimantas Belevičius; Dainius Rusakevičius; Saulius Valentinavičius (Advances in Civil Engineering)
The main objective of the article is to find the optimal ranges of the cardinal topological, shape, and dimensional parameters that fully describe the constructional scheme of pedestrian radial network arch bridges of moderate spans. This task is solved by formulating the global optimization problem and seeking the minimum mass of the whole bridge structure. An optimal bridge scheme was obtained by tuning a large set of interdependent design parameters of diverse character: the topological parameters–the type of hanger arrangement, and the number of hangers; the shape parameters–hanger spread and central section angles, the alteration of these angles, and the arch rise; and the sizing parameters–all cross-sectional dimensions of structural members. Mathematically, this is a constrained mixed-integer global optimization problem solved by a stochastic evolutionary algorithm. Plane light-deck bridges of typical moderate 30, 45, 60, 75, and 90 m spans were optimized. Decisive design parameters and their rational ranges for all spans were revealed. In addition, the effects of some simplifications of the general bridge scheme were shown: using the constant spread and central section angles; imposing certain values on the ratio arch rise/bridge span; bounding the hanger diameters to a given value; and so on. Obtained results clearly indicate that the design recommendations for the lightweight network arch bridges should differ from the recommendations for similar automotive and railway bridges. Our findings are: the optimal ratio of arch rise to the bridge span is 0.20–0.30, the number of hangers is >40 even for the shortest spans, the spread angle between hangers is 30°–40°, and the girder mass amounts to ∼30% of the total bridge mass, while the mass of hangers amounts up to 20% and increases when imposing constraints on the minimal radius at the expense of diminishing arch mass.